Identification of orally-bioavailable antagonists of the TRPV4 ion-channel. Issue 18 (15th September 2015) - Wei, Zhi-Liang; Nguyen, Margaret T.; O'Mahony, Donogh J.R.; Acevedo, Alejandra; Zipfel, Sheila; Zhang, Qingling; Liu, Luna; Dourado, Michelle; Chi, Candace; Yip, Victor; DeFalco, Jeff; Gustafson, Amy; et al.
Graphical abstract: Abstract: Antagonists of the TRPV4 receptor were identified using a focused screen, followed by a limited optimization program. The leading compounds obtained from this exercise, RN-166523 and RN-989326, showed moderate oral bioavailability when dosed to rats. The lead molecule, RN-989326, inhibited human, rat and murine variants of TRPV4, and showed excellent selectivity over related TRP receptors, such as TRPV1, TRPV3 and TRPM8. The overall profile for RN-9893 may permit its use as a proof-of-concept probe for in vivo applications.